Pengaruh Peer support, Teacher Support, dan Digital Literacy terhadap Student Engagement dengan Self Regulated Learning sebagai Pemediasi - Mahardika, Aura Aglis; Ahmad Nurkhin (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2024)
This study aims to analyze the influence of peer support, teacher support, and digital literacy on student engagement through self-regulated learning in Economics Education students, Faculty of Economics and Business, State University of Semarang Class of 2020. This study uses a quantitative approach with a sample of 161 students. The sampling technique is to use saturated samples. The data collection method used a questionnaire with data analysis using descriptive statistical analysis and Structural Equation Modelling-Partial Least Square (SEM PLS) analysis. The analysis tool used in this study is SmartPLS 4.0. The results of the analysis show that peer support, teacher support, and digital literacy have an effect on student engagement through self-regulated learning.